2022
DOI: 10.3390/cells11071183
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Profile of Major Dysmood Disorder: Proof of Concept and Mechanism Using the Precision Nomothetic Psychiatry Approach

Abstract: Major depressive disorder and a major depressive episode (MDD/MDE) are characterized by activation of the immune-inflammatory response system (IRS) and the compensatory immune-regulatory system (CIRS). In MDD/MDE, recent precision nomothetic psychiatry studies discovered a new endophenotype class, namely major dysmood disorder (MDMD), a new pathway phenotype, namely reoccurrence of illness (ROI), and a new model of the phenome of depression. The aim of the present study is to examine the association between RO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
147
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(156 citation statements)
references
References 58 publications
(109 reference statements)
8
147
1
Order By: Relevance
“…There is now evidence that MDD is characterized by activation of the immune-inflammatory response system (IRS) with activation of M1 macrophage, T helper (Th)-1 and Th-17 phenotypes and increased production of growth factors, including platelet derived growth factor (PDGF) (Maes and Carvalho, 2018; Maes et al, 2022a). Some cytokines and chemokines that are overproduced in MDD, such as interleukin (IL)-15, IL-17, IL-1β, IL-6, tumor necrosis factor (TNF)-α, interferon (IFN)-γ, CXCL8, CXCL10, and CCL5, have neurotoxic effects and may jeopardize neuronal functions, such as neurogenesis, neuroplasticity, receptor expression, axonogenesis, and dendritic sprouting (Maes et al, 2022a; Maes et al, 2009). Moreover, elevated levels of IL-6, IL-1β, and TNF-α induce an acute phase response in the liver, leading to increased production of C-reactive protein (CRP) (Sluzewska et al, 1996), which has additional toxic effects on endothelial cells, thereby increasing the permeability of the blood-brain barrier (BBB) and exacerbating the development of neurodegenerative and cerebrovascular processes (Belin et al, 2020; Ge et al, 2013; Hsuchou et al, 2012; Song et al, 2009; Windgassen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is now evidence that MDD is characterized by activation of the immune-inflammatory response system (IRS) with activation of M1 macrophage, T helper (Th)-1 and Th-17 phenotypes and increased production of growth factors, including platelet derived growth factor (PDGF) (Maes and Carvalho, 2018; Maes et al, 2022a). Some cytokines and chemokines that are overproduced in MDD, such as interleukin (IL)-15, IL-17, IL-1β, IL-6, tumor necrosis factor (TNF)-α, interferon (IFN)-γ, CXCL8, CXCL10, and CCL5, have neurotoxic effects and may jeopardize neuronal functions, such as neurogenesis, neuroplasticity, receptor expression, axonogenesis, and dendritic sprouting (Maes et al, 2022a; Maes et al, 2009). Moreover, elevated levels of IL-6, IL-1β, and TNF-α induce an acute phase response in the liver, leading to increased production of C-reactive protein (CRP) (Sluzewska et al, 1996), which has additional toxic effects on endothelial cells, thereby increasing the permeability of the blood-brain barrier (BBB) and exacerbating the development of neurodegenerative and cerebrovascular processes (Belin et al, 2020; Ge et al, 2013; Hsuchou et al, 2012; Song et al, 2009; Windgassen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They are highly expressed at the embryonic stages (especially JAK2, JAK1, STAT3, STAT6 and STAT1), and their expression gradually decreases during growth and adulthood [ 21 , 22 , 23 ]. Recently, a protein–protein interaction network analysis showed that the activation of JAK-STAT signaling is an important pathway underpinning the immune disorders in major depression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…From our results, GTF2F2 may affect the TGF-β pathway through NRF-1, and therefore, associate with MDD progression. Besides, JAK-STAT signaling pathway was reported in the MDD ( Gao et al, 2022 ; Maes et al, 2022 ), which may also act as a target of GTF2F2 affecting MDD.…”
Section: Discussionmentioning
confidence: 99%